O desenvolvimento da criança surda sob a perspectiva de profissionais bilíngues: um estudo de caso - Medeiros, Bianca Aparecida (Universidade Federal de São Carlos, 2022)
The present research aimed to understand how the development of language by the deaf child takes place from the speech of two bilingual professionals: deaf instructor of Libras and bilingual teacher, for that, a qualitative research was used with a case study that was carried out through an online interview with two bilingual education professionals. Through this, understood the importance of both professionals in the school environment was understood, helping in the process of acquiring language, culture and identity of the deaf child. However, it is understood that there are still challenges present with in the school environment, such as the lack of specific training for both professionals and the family’s understanding of the acquisition of sign language by the deaf child.
The development of deaf children from the perspective of bilingual professionals: a case study
Keywords: Aquisição de linguagem; Instrutor de Libras; Professor bilíngue de Libras; Surdez; Educação Especial; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO